Blood-to-saliva glucose time lag in sedated healthy dogs. (November 2021) - Ioannou, Antonia; Phillips, Heidi; Keating, Stephanie; Barger, Anne; Lopez-Villalobos, Nicolas; Wilson, Macy; Dillonaire, Alyssa; Silveston-Keith, Rebecca; Ambrisko, Tamas D.; Gal, Arnon
The management of diabetes mellitus mandates measurement of blood glucose. Saliva offers an alternative to blood sampling, but measurement of the salivary glucose concentration is difficult, and the blood-to-saliva glucose time lag is uncertain. We aimed to determine the serum–saliva glucose time lag in the saliva of healthy dogs. The combined duct of the mandibular and sublingual salivary glands of 6 dogs was cannulated to collect saliva and prevent glucose degradation by oral bacteria. Following a 0.25 g/kg IV bolus of dextrose, paired serum–saliva samples were collected at baseline and in twelve 5-min blocks over 60 min. Serum and salivary glucose levels were analyzed with a linear mixed model for repeated measures with a compound symmetry error structure. Mean (±SD) saliva production was 10.3 ± 2.9 µL/kg/min, and the area under the curve (AUCglucose )saliva/serum ratio was 0.006, which highlights the magnitude of the large difference in glucose concentration between the 2 compartments. The serum–saliva glucose time lag was 30–40 min.